FACTORS OF FORMATION AND IMPROVEMENT OF VOCAL SINGING SKILLS THROUGH FOLKLORE SONGS - Mamarasulzoda Zulxumor Abdulqosimovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article explores the factors influencing the development and enhancement of vocal singing skills through the use of folklore songs. By analyzing the pedagogical, cultural, and technical aspects of folklore singing, the study highlights the role of traditional music in building vocal techniques, emotional expression, and cultural awareness. The findings underscore the pedagogical value of integrating folklore into modern music education.